Predictive value of transcranial doppler ultrasound for cerebral small vessel disease in elderly patients - Fu, Shengqi; Zhang, Jiewen; Zhang, Hongtao; Zhang, Shuling (Arquivos de Neuro-Psiquiatria, 2019)
Objective: To investigate the predictive value of transcranial Doppler (TCD) ultrasound for cerebral small vessel disease in elderly patients.Methods: Transcranial Doppler ultrasound and magnetic resonance imaging (MRI) were performed on 184 elderly patients with cerebral small vessel disease. The relationship of clinical characteristics and TCD ultrasound parameters with severe white matter lesions (WMLs) in MRI were investigated by univariate analysis and multivariate analysis.Results: The univariate analysis showed that age, left middle cerebral artery (MCA) mean flow velocity, right MCA mean flow velocity and mean MCA pulsatility index were significantly correlated with severe WMLs (p < 0.05). The multivariate logistic regression analysis showed that only age (odds ratio: 1.21; 95%CI: 1.10–1.36; p < 0.01) and MCA pulsatility index (dominance ratio: 1.13; 95%CI: 1.06–1.80; p = 0.02) were significantly correlated with severe WMLs. The analysis of TCD ultrasound parameters showed that when the cut-off for MCA pulsatility index was 1.04, it could identify severe WMLs. The area under the curve was 0.70 (95%CI: 0.60–0.80). The sensitivity and specificity were 63.0% and 72.0%, respectively. The positive and negative predictive values were 35.4% and 86.6%, respectively.Conclusion: The MCA pulsatility index in TCD ultrasound is significantly correlated with severe WMLs; and TCD ultrasound can guide selective MRI for the detection of WMLs.
Keywords: Cerebral small vessel disease; ultrasonography, transcranial doppler